A EXPANSÃO DO ENSINO SUPERIOR E O FINANCIAMENTO DAS INSTITUIÇÕES FEDERAIS: a experiência brasileira na dinâmica da relação público/privado no período de 2003 a 2014. - SILVA, Raphael Bruno Bezerra (2019)
The objective of this study is the expansion of Brazilian higher education, from 2003 to 2014, which, based on its assumptions, saw an economic policy that affected the resources that went to the federal institutions of higher education. The central hypothesis is that the so-called neoliberal policy plays a predominant role in the incentive action of private higher education institutions, also associated with the impacts on the effective allocation of the Union's budgetary resources for the financing of federal public universities. Brazilian public higher education has undergone a period of intense crisis, which is a result of structural actions, consolidated, above all, from the Fernando Henrique Cardoso government and aligned with the guidelines of the multilateral organizations, which propose that underdeveloped countries such as Brazil, seek the budget balance by reducing public spending and the predilection for private education, which would be essentially technical, efficient and self-sustaining. These changes would act as inducers of national economic growth through fiscal balance and scientific and technological progress. The private priority represented the public universities a policy of rationalization of funds and greater collections to meet the diverse demands and desires of capital. From 2003 to 2014, there were, in certain aspects, continuity of the policy of commercial expansion through the adoption of mechanisms such as: public / private partnership policies; financial liberalization and educational services; tax exemptions; exemption from the social security contribution of philanthropic institutions; fellowships for students via FIES; financial loans at interest subsidized by official banking institutions, such as the National Bank for Economic and Social Development (BNDES), and ProUni. To answer the following questions: "In terms of the public / private relationship, has there been a deliberate action by the State to promote the commodified expansion of higher education? and what is the impact of neoliberal actions regarding the allocation of resources to federal universities? "The aim was to understand the double aspect imbued in the priorities defined in public policies and the allocation of the budgetary resources of the Union. To that end, of the bibliographic research and the examination of official documents, the contribution of Budget Execution Statements, between 2003 and 2014, made available by the Federal Senate, and of the INEP database of the Census of Higher Education (2003 - 2014). The study showed that the policy of expanding higher education has favored the private sector through government incentives. The descriptive analysis of laws, decrees, data on the expansion of education, the evolution of resources destined to the IFES and their comparison with the other channels of destination considered as priority, such as the payment of interest of the public debt, showed that the governments that acted in Recent periods have not only kept the national pattern dependent but made it possible to deepen it. As a result of this action, the Brazilian higher education system in 2014 was formed by 92% of isolated educational institutions and only 8% of universities, 87.4% of private institutions and 12.6% of public institutions.